Analisis Pembelajaran 4 Gerakan Tari Payung untuk Siswa Tunarungu Kelas VI di SLB Negeri Tamansari Kota Tasikmalaya - Rafifah, Rifa; Ahmad Wakih, Agus; Heris Mahendra, Hatma (Indo-MathEdu Intellectuals Journal, 2024)
Dance arts are related to movement and musical rhythm, with a strong connection to hearing. This research is motivated by the researcher’s interest in the abilities of deaf students who can synchronize their movements with musical rhythms to achieve excellence. The purpose of this study is to describe the teaching methods, the four movements of Tari Payung, and the interest of deaf students in dance arts at SLB Negeri Tamansari in Tasikmalaya City. This research uses a qualitative method with a descriptive approach. Data collection techniques use triangulation to combine various data sources and techniques. Qualitative research aims to understand phenomena related to behavior, motivation, perception, and actions of subjects holistically. The research findings indicate that deaf students have a good interest in learning dance arts. Students demonstrate interest, enjoyment, attention, active participation, and good awareness. This is evident from their consistent attendance, enthusiasm during practice, and the achievements they have attained in dance arts education.